Pulmonary Abscess as a Complication of SARS-CoV-2 Pneumonia - Uzer, Fatih; Oner, Sukriye; Cilli, Aykut (Libyan International Medical University Journal, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease originated in the Wuhan region of China and spread all over the world. This disease typically starts as an acute viral disease, and it is characterized by lung infiltrates and elevation of inflammatory markers. The definitive diagnosis of the disease is confirmed by polymerase chain reaction (PCR) results. Although majority of patients with positive PCR results had mild disease, 5 to 14% of them are severely affected. It has been reported in the literature that a significant proportion of adult patients develops virus-related complications. Lung abscess is one of these complications that is a suppurative infection with an air-fluid level greater than 2 cm in diameter on chest X-ray. Although there is usually a single cavity, it can also be multifocal. It was reported as a possible late-term complication of SARS-CoV-2. We are presenting two cases with lung abscess after SARS-CoV-2 treatment.
Keywords: SARS-CoV-2; lung abscess; pandemic